Perancangan Sistem Pengajuan Infrastruktur dan Aplikasi di Kementerian Pendidikan Dasar dan Menengah Menggunakan UML (Unified Modeling Language) - Imron, Muhammad Nursalim; Rinusantoro, Sonasa (Jurnal Riset Informatika dan Inovasi, 2026)
The process of submitting infrastructure and application proposals within the Ministry of Primary and Secondary Education requires a structured mechanism to ensure alignment with Electronic-Based Government System (SPBE) policies and to support the efficient management of ICT budgets. In practice, submission processes that remain manual and fragmented may lead to challenges in tracking status, maintaining data consistency, and synchronizing planning and budgeting.This study aims to design a web-based infrastructure and application submission system capable of supporting an integrated ICT planning and budgeting clearance process. The method employed is a system design approach using Unified Modeling Language (UML), which includes modeling functional and non-functional requirements, business process modeling, and database design. The UML diagrams utilized in this study consist of Use Case Diagrams, Activity Diagrams, Sequence Diagrams, Class Diagrams, State Diagrams, and Entity Relationship Diagrams (ERD). Additionally, the user interface design is developed in the form of mockups to provide an initial overview of system interaction flows and interface layout.The results of this study present a system design that encompasses the submission workflow, verification and validation processes, as well as decision-making procedures within the clearance process. This design is expected to serve as a foundation for developing a more structured, well-documented infrastructure and application submission system aligned with organizational needs.